Organic Multiheterojunctions: Revelation of Interfacial Energetics in Organic Multiheterojunctions (Adv. Sci. 4/2017). Issue 4 (19th April 2017) - Kästner, Christian; Vandewal, Koen; Egbe, Daniel Ayuk Mbi; Hoppe, Harald
Abstract : Christian Kästner and co‐workers demonstrate the existence of several charge transfer transitions within one single organic semiconductor bulk heterojunction in article number1600331 . The cover depicts an organic polymer solar module ‐ illuminated by the sun. A magnifying lens focusses deep into the internal structure of the organic semiconductor bulk heterojunction. Different domains of pristine (semi‐crystalline or amorphous) polymer, pristine (semi‐crystalline) fullerene derivative or an amorphous blend of the two are shown. The flashing lights depict various radiative recombination pathways for electrons and holes across interfaces exhibiting differently ordered materials, which have different emission energies – as indicated by various colors.